Three decades of survival in Pancreatic Neuroendocrine Tumor with Unresectable Liver Metastases - Maddibande Ramachar Sreevathsa; Nishnata Koirala (Annals of Pancreatic Disorders and Treatment - Peertechz Publications, 2018)
Pancreatic neuro-endocrine tumors are rare and have a slow growth rate. They have long-term survival even when associated with hepatic metastases, after organ directed surgical treatment. Several prognostic factors have been identified for survival in pancreatic neuro-endocrine tumors with or without liver metastases. We describe a 32-year-old male patient with BMI of 16.4, presenting initially with recurrent, multiple, peptic ulcers and later carcinoid syndrome. A pancreatic neuro-endocrine tumor with synchronous bilobar liver metastases was discovered on laparotomy. The primary tumor was 7.5 centimeter in size, low-grade and well differentiated variety. Chromogranin A level was 81ng/liter (normal 39ng/liter) and Ki67 expression was 3%. The serum 5-Hydroxy indole acetic acid was 3246ng/ml(normal 0-22ng/ml), 24 hour urinary 5-hydroxy indole acetic acid was 1742 mg (normal 0-2.7mg) , serum gastrin level was 1060 pg/ml (normal <100pg/ml) and patient is on long-term omeprazole maintenance therapy. He has survived for 32 years without organ directed surgical treatment. Literature is briefly reviewed.